The Response of Readers in the Novel The Call of The Wild - Andi Febriana Tamrin; Basri; Ayuningtyas Eka Putri (Surakarta English and Literature Journal, 2023)
This research is to investigate readers' responses to the novel The Call of The Wild, focusing on its intrinsic elements. Employing a voluntary sampling strategy within the Telegram Reader Group, ten participants were selected to collect the data through a questionnaire, which was analysed in line with Jauss' theory. Qualitative descriptive methodology was employed, to understand readers' reactions to the novel's key components, including theme, plot, setting, character, and characterization. The research's implications are multifaceted: it enriches our comprehension of how readers interpret intricate literary elements, demonstrating the interplay between authorial intent and reader understanding. This research underscores the value of intrinsic elements in shaping reader engagement, offering insights applicable to authors, educators, and enthusiasts. The research's design showcases the feasibility of voluntary sampling in online reader communities and introduces a systematic approach to analysing reader responses through tailored questions. Overall, this research contributes to our understanding of reader interactions with literature, spanning realms from narrative interpretation to research methodology.